Foodborne Lactic Acid Bacteria Inactivate Planktonic and Sessile Escherichia coli O157:H7 in a Meat Processing Environment: A Physiological and Proteomic Study - Cisneros, Lucia (2025)
Enterohemorrhagic Escherichia coli (EHEC) forms persistent biofilms on meat processing surfaces, posing a significant cross-contamination risk. This study assessed the antagonistic capacity of lactic acid bacteria (LAB) against EHEC under meat-processing-like conditions. Three LAB strains were tested in planktonic co-culture with EHEC at 12 ◦C, all displaying bactericidal activity. In biofilm assays on stainless steel, LAB reduced EHEC biofilms without affecting their own viability. LAB cell-free supernatants further inhibited EHEC biofilms by 2.6–3.5 log CFU/cm2, highlighting the role of secreted antagonistic compounds. Among the tested strains, Pediococcus pentosaceus CRL 2145 showed the strongest effect and was selected for deeper analysis. Fluorescence microscopy confirmed EHEC cell death within mixed biofilms. Proteomic profiling of CRL 2145 under mixed-biofilm conditions revealed 162 differentially expressed proteins, with 156 upregulated. These proteins were mainly associated with metabolism, transcription, translation, and stress response pathways, suggesting a multifactorial inhibitory mechanism involving metabolic dominance, physical competition, and secretion of antagonistic molecules. Overall, this study deepens our understanding of the molecular and physiological aspects of LAB–EHEC interaction. P. pentosaceus CRL 2145 emerges as a promising biocontrol agent that could be applied, alone or with its supernatants, to meat processing surfaces to improve food safety. Proteomic data: ProteomeXchange PXD067300.